The Power of Emak-Emak: Perempuan dalam Pusaran Kampanye Politik Pemilihan Presiden 2019 - Mahyuddin Mahyuddin; Emilia Mustary; Nisar Nisar (LPPM IAIN Parepare, 2019)
This research describe the militancy shown by women in the presidential election at 2019 in Indonesia. This paper aimed to explore women's political participation in presidential elections at 2019. The research approach used Critical Discourse Analysis (CDA) in the construction of the power of emak-emak (motherhood). The author explored a series of political actions by a group of mothers who were skilled at producing unique song texts and interesting political campaigns as an expression of support for one of the candidates. These findings indicated that the role of women in current general election was increasingly apparent by involved joining creative campaigns, controling government policies, and giving voice of women`s independence. One side of the political activities is a form of democratic maturity phase, but on the other hand cannot be separated from the power and authority relation of the opposition groups.